Do Routine Laboratory Parameters have Predictive Ability to Differentiate Subjects with Fibromyalgia from Healthy Subjects?. (January 2023) - Rus, Alma; Molina, Francisco; Camacho, María Victoria; Rubia, Mercedes La; Aguilar-Ferrándiz, María Encarnación; del Moral, María Luisa
The aim of this study was to evaluate laboratory parameters for investigating their potential predictive ability to differentiate patients with fibromyalgia (FM) from healthy subjects. We carried out a case–control study with 79 FM patients and 20 controls to analyze complete blood count, serum chemistry profile, glycosylated hemoglobin (HbA1c), and erythrocyte sedimentation rate (ESR). The predictive value of these parameters was determined by receiver operating characteristic (ROC) analysis. We also examined the relationships with clinical parameters (functional capacity, pain, and physical and mental health status). Results showed significant differences in red blood cell count, hematocrit, mean corpuscular hemoglobin concentration, platelet count, creatinine, HbA1c, and ESR between groups. According to ROC analysis, all these parameters may assist in making FM diagnosis. Hematocrit and ESR values were correlated with FM clinical parameters. The determination of these routine laboratory parameters may be an uncomplicated means of facilitating FM diagnosis, together with the clinical data of the patient.